Carbon monoxide supplementation: evaluating its potential to enhance altitude training effects and cycling performance in elite athletes - Urianstad, T.; Villanova, S.; Odden, I.; Hansen, J.; Mølmen, K. S.; Porcelli, S.; Rønnestad, B. R.; Cardinale, D. A. (Journal of Applied Physiology, 2024)
Altitude training is a cornerstone for endurance athletes for improving blood variables and performance, with optimal effects observed at ~2,300-2,500 meters above sea level (m.a.s.l.). However, elite cyclists face challenges such as limited access to such altitudes, inadequate training facilities, and high expenses. To address these issues, a novel method involving daily exposure to carbon monoxide (CO) has been proposed to amplify altitude training adaptations at suboptimal altitudes. Thirty-one male cyclists were assigned to three groups: Live-High Train-High with CO inhalation (LHTHCO), Live-High Train-High (LHTH), and Live-Low Train-Low (LLTL). The LHTHCO group underwent CO inhalation twice daily in the afternoon/evening to elevate carboxyhemoglobin concentration to ~10%. Hematological variables, in vivo muscle oxidative capacity, and physiological indicators of cycling performance were assessed before and after a 3-week altitude training camp at 2,100 m.a.s.l. LHTHCO demonstrated a larger increase in hemoglobin mass (Hbmass) compared to both LHTH and LLTL. Although there were no statistical differences between LHTHCO and LHTH in submaximal and maximal performance measures, LHTHCO displayed greater improvements in 1-min maximal power output during incremental testing (Wmax), power output at lactate threshold, and maximal oxygen consumption (Vo2max) compared to LLTL. LHTH demonstrated a larger improvement than LLTL in Wmax and Vo2max, with no group differences in Hbmass or submaximal measures. Muscle oxidative capacity did not differ between groups. These findings suggest that combining moderate-altitude training with daily CO inhalation promotes hematological adaptations more effectively than moderate altitude alone and enhances cycling performance metrics in cyclists more than sea-level training.